Exponential increment of RSA attack range via lattice based cryptanalysis - Nitaj, Abderahmanne; Ariffin, Muhammad Rezal Kamel; Adenan, Nurul Nur Hanisah; Ahmadian, Ali; Merenda, Domenica Stefania (Springer, 2021)
The RSA cryptosystem comprises of two important features that are needed for encryption process known as the public parameter e and the modulus N. In 1999, a cryptanalysis on RSA which was described by Boneh and Durfee focused on the key equation and e of the same magnitude to N. Their method was applicable for the case of via Coppersmith’s technique. In 2012, Kumar et al. presented an improved Boneh-Durfee attack using the same equation which is valid for any e with arbitrary size. In this paper, we present an exponential increment of the two former attacks using the variant equation . The new attack breaks the RSA system when a and |c| are suitably small integers. Moreover, the new attack shows that the Boneh-Durfee attack and the attack of Kumar et al. can be derived using a single attack. We also showed that our bound manage to improve the bounds of Ariffin et al. and Bunder and Tonien.